2019
DOI: 10.1017/dsi.2019.227
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges of Agile Hardware Development: What are Still the Pain Points Nowadays?

Abstract: Originally developed for the software industry, agile development is being applied in the hardware field nowadays as well due to its benefits when having to deal with volatile, uncertain, complex and ambiguous (VUCA) conditions. However, certain complications arise when applying the concept of agility in the hardware. In this publication, based on the challenges identified by Ovesen in 2012, the current challenges of agile development for hardware are gathered using an embedded design approach, ensuring its ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…scaling agile) was still not achieved in this organization by the time this research was conducted. Unlike [5] study where mindset and team distribution were revealed as additional challenges in hardware development, in this study this factor were not challenging. Instead, the agile mindset of top management and the team co-location had a positive influence on implementing LAPM in this organization.…”
Section: Rq1: What Were the Key Success Factors And What Were The Chamentioning
confidence: 85%
See 1 more Smart Citation
“…scaling agile) was still not achieved in this organization by the time this research was conducted. Unlike [5] study where mindset and team distribution were revealed as additional challenges in hardware development, in this study this factor were not challenging. Instead, the agile mindset of top management and the team co-location had a positive influence on implementing LAPM in this organization.…”
Section: Rq1: What Were the Key Success Factors And What Were The Chamentioning
confidence: 85%
“…Similarly to this research, [11] research considers lack of teamwork and resistance from groups or individuals as key people factors that could cause the failure of the agile implementation. Like [5] study suggests that one of the main challenges in hardware development is realizing potentially shippable increments in one iteration, these teams also struggled to deliver functionality within regular time-box (Sprint). Although increments were a Scrum artifact in SSA projects, the team did not deliver them within Sprint but rather in irregular periods based on the needs of customer and their possibilities.…”
Section: Rq1: What Were the Key Success Factors And What Were The Chamentioning
confidence: 99%
“…There are many different agile methods available for software development, among the most popular being: Scrum, Kanban, eXtreme Programming (XP), Crystal methods, and others (Atzberger and Paetzold, 2019). All the methods share the same idea of continuous value delivery and responsiveness to changes, but differ in the depth of guidance and breadth of the life cycles.…”
Section: Agile Development and Scrummentioning
confidence: 99%
“…As the project teams are empowered to make their own decisions, management can feel as they have lost the power. This issue is also referred to as the ''prince problem'' (Atzberger and Paetzold, 2019).…”
Section: Potential Implementation Issuesmentioning
confidence: 99%
See 1 more Smart Citation